Bench evaluation of commercially available and newly developed interfaces for mouthpiece ventilation. (9th January 2017) - Ogna, Adam; Prigent, Helene; Falaize, Line; Leroux, Karl; Santos, Dante; Vaugier, Isabelle; Orlikowski, David; Lofaso, Frederic
Abstract: Introduction: Mouthpiece ventilation represents a valuable treatment for patients needing daytime non‐invasive ventilation. This modality is however underused, in part because of limitations in the available equipment. Objective: To develop a new flexible and moldable mouthpiece, aiming to address some of the issues of the currently available interfaces. Methods: We compared two commercially available and the newly developed mouthpieces in a bench test using four life‐support home ventilators and three settings per ventilator. Results: The three interfaces showed marked differences in their resistive characteristics. In the volume‐controlled setting (VC‐CMV) with 500 mL tidal volume ( V T ), the delivered V T, ranged between 459 ± 7 mL (−8%) and 501 ± 4 mL (+0.2%), according to the used ventilator. In the VC‐CMV setting with V T 1000 mL, one of the ventilators did not assure the set V T with the new mouthpiece, because of the high‐pressure limitation. In the pressure‐controlled setting (PC‐CMV at 20 cmH2 O), the effective pressure differed between the tested interfaces according to their resistance, resulting in a decrease in the delivered V T . Conclusions: They found measurable differences in the ventilation's performances comparing the interfaces for mouthpiece ventilation, which seem to have a minor clinical relevance in the most settings, but should be systematically checked. They validated in‐vitro the newly developed mouthpiece with respect to the ventilation performances; a clinical study is needed to investigate the potential advantages we expect from the new mouthpiece.